USE OF INTERNATIONAL EXPERIENCES IN TEACHING ENGLISH (International journal of artificial intelligence, 2024)
Modern globalization processes make learning English more important and necessary. English is not only the language of international communication, but also plays an important role in business, science and culture. Therefore, it is important to use international experiences in teaching English, to improve the quality of education and to increase students' interest in the language. This article provides information about international experiences in teaching English, their advantages and how they are used in the Uzbek context.